Abortion and the basis of equality: a reply to Miller - Bozzo, Alexander (Journal of medical ethics, 2024)
Miller has recently argued that the standard liberal and moderate positions on abortion are incapable of grounding the claim that ‘all non-disabled adult humans are equal’. The reason, he claims, is such accounts base the intrinsic moral worth of a human being on some property (or set of properties) which comes in degrees. In contrast, he argues that moral equality must reside in some binary property, such as the property of being human. In this paper, I offer three criticisms of Miller’s position.